The "Cold Open" as a Method for Launching a Course. (December 2019) - O'Brien, James
The "cold open" is a literary technique that can be usefully adapted for management education, particularly as an opening exercise on the first day of class. Specifically, this approach includes presenting a carefully chosen problem to the class without preamble, providing students an opportunity to work on the problem, and perhaps most important, conducting a debrief that is focused on schema construction for the course and that identifies and builds on the current level of understanding on the part of the students. The "cold open" allows the instructor to begin to surface concepts that support the construction of schema, which is in turn linked to transfer of learning and the emergence of expertise. This article includes a worked example of "cold open, " including debriefing questions, and additional sample problems for instructors who wish to incorporate this technique into their teaching repertoires.